The Dynamic of Smoking Behavior through the Course of Tuberculosis Illness: A Hospital-Based Study in Medan, Indonesia - Safira, Nanda; Wichaidit, Wit; Chongsuvivatwong, Virasakdi (Faculty of Medicine Universitas Airlangga, 2024)
Introduction: Smoking is associated with the prognosis of tuberculosis (TB). The diagnosis of TB in patients who smoke or recently quit smoking can be a pivotal moment that motivates them to continue quitting smoking. However, there is a paucity of information on changes in smoking status among TB patients through the course of the disease. This study presented self-report smoking status during the pre-symptomatic, post-symptomatic, intensive treatment, and continuation treatment phases among TB patients receiving treatment. Methods: This was a cross-sectional study conducted at four hospitals in Medan, Indonesia, from December 2019 to February 2020. For at least one month, healthcare workers invited TB patients who had received treatment at the hospitals' TB-Directly Observed Treatment Shortcourse (DOTS) clinics to participate in this study. Trained enumerators collected the data through face-to-face interviews, in which the patients self-reported information on their smoking status at various phases. Results: Of 285 patients who met the inclusion criteria, 277 gave their consent (97% participation), of whom 146 never smoked in their lifetime. Among 131 ever smokers, 88 (67%) had quit smoking before or during the pre-diagnosis phase, 65 (51.6%) of whom remained quitters throughout the course of the disease. Thirty-eight patients continued to smoke after symptom onset, and more than half of them had stopped smoking by the continuation phase of treatment. Conclusion: Smoking cessation was relatively common after the appearance of TB symptoms and after diagnosis. However, some patients subsequently relapsed, while others were unable to quit smoking. Social desirability could have influenced the responses and should be considered in interpreting the study findings.